Associations of modifiable risk factors with all-cause and cardiovascular disease deaths: a linkage study among adult community hypertension patients in Hangzhou city - Shijun LIU; Yan ZHANG; Caixia JIANG; Jue XU; Xin QIU; Jun LUO; Bing LIU (Editorial Office of Chinese Journal of Public Health, 2023)
ObjectiveTo analyze correlations of modifiable risks with all-cause deaths and cardiovascular disease (CVD) deaths in hypertension patients. MethodsComprehensive data of 2015 on 51 438 community hypertensive patients aged 35 - 85 years were extracted from the management information system of Essential Public Health Services and were linked to individual records of mortality in the datasets of death registry system up to February 28, 2021 in Hangzhou municipality, Zhejiang province. Cox proportional regression model was used to estimate hazard risks of all-cause and CVD deaths associated with modifiable risk factors of the mortalities. ResultsBy the end of study period, totally 2 365 all-cause and 842 CVD deaths were observed among the participants and the mortality ratios were 4.60% and 1.64%, respectively. Of the 51 438 hypertensives, 3 926 (7.63%), 20 392 (39.64%), 20 292 (39.45%), and 6 828 (13.28%) were assessed as having none, one, two, and three and more modifiable risk factors of CVD. The results of Cox proportional regression analysis showed that after adjusting for gender, age, living region, migration, and diabetes, the hypertensives being lack of good blood pressure control (systolic blood pressure [SBP] of ≥ 140 mmHg/diastolic blood pressure (DBP) of ≥ 90 mmHg at three measurements not in the same day) were at significantly increased risks of all-cause death (hazard risk [HR] = 1.39) and CVD death (HR = 1.52) compared to those under effective blood pressure control (SBP < 140 mmHg/DBP < 90 mmHg); the hypertensives being current smoker had significantly increased risks of all-cause death (HR = 1.21) and CVD death (HR = 1.24) contrasting to nonsmoking hypertensives; the hypertensives not having daily physical exercise were at significantly increased risks of all-cause death (HR = 1.52) and CVD death (HR = 1.73) in comparison to those reporting daily physical exercise; the results also revealed significantly increased risks of all-cause death (HR = 1.53, HR = 1.69, and HR = 1.97) and CVD death (HR = 2.32, HR = 2.35,and HR = 2.94) for the hypertensives with one, two, and three modifiable risk factors compared to those without any modifiable risk factor; while, the obese hepertensives had a significantly decreased risk of all-cause death (HR = 0.84) compared to the non-obese hypertensives. ConclusionThe risks of all-cause and CVD death increased with the number of modifiable risk factors among adult community hypertension patients.